The influence of biological maturity on sprint speed, standing long jump, and vaulting performance in young female gymnasts - Moeskops, S.; Oliver, J. L.; Read, P. J.; Myer, G. D.; Lloyd, R. S. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To quantify speed, peak momentum, standing long jump (SLJ), and the ratio of vertical to horizontal take-off velocity (Ratiovert-hori TOV) in young female gymnasts of different maturity status and their influence on vaulting vertical TOV.